Kinetics of Synaptic Transmission at Ribbon Synapses of Rods and Cones - Thoreson, Wallace B. (2007)
The ribbon synapse is a specialized structure that allows photoreceptors to sustain the continuous release of vesicles for hours upon hours and years upon years but also respond rapidly to momentary changes in illumination. Light responses of cones are faster than those of rods and, mirroring this difference, synaptic transmission from cones is also faster than transmission from rods. This review evaluates the various factors that regulate synaptic kinetics and contribute to kinetic differences between rod and cone synapses. Presynaptically, the release of glutamate-laden synaptic vesicles is regulated by properties of the synaptic proteins involved in exocytosis, influx of calcium through calcium channels, calcium release from intracellular stores, diffusion of calcium to the release site, calcium buffering, and extrusion of calcium from the cytoplasm. The rate of vesicle replenishment also limits the ability of the synapse to follow changes in release. Post-synaptic factors include properties of glutamate receptors, dynamics of glutamate diffusion through the cleft, and glutamate uptake by glutamate transporters. Thus, multiple synaptic mechanisms help to shape the responses of second-order horizontal and bipolar cells.